Legal Simplification of Land Regulation Associated with Increased Investment as the Basis for Conceptualization of the Omnibus Law - TARMIZI, TARMIZI (Journal of Advanced Research in Law and Economics; Vol 11 No 1 (2020): JARLE Volume XI Issue 1(47) Spring 2020DO - 10.14505//jarle.v11.1(47).24, 2020)
The inhibiting factor for the improvement of the investment climate in Indonesia is due to the many overlapping regulations. Regulatory problems are related to a number of fields including regulations on defense. Indonesia's land policy is still unstable and often changes according to the wishes and interests of the authorities. The problem of land is a complex national problem mainly because it involves the lives of many people. Land is a means of production and helps guarantee the welfare of the people. Nowadays a breakthrough is needed, namely the need for Omnibus Law. One of the strengths of the Omnibus Law is that there will be a law under the affairs of various different ministries. This will speed up the consolidation of unprofitable and conflicting rules all at once. The idea of the Omnibus Law concept is expected to be able to resolve regulatory conflicts in the land sector and is expected to be effective in resolving long-standing regulatory conflicts.